2019
DOI: 10.2176/nmc.cr.2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of MRI Slices Parallel to the Optic Chiasma in a Case with Traumatic Optic Nerve Avulsion after a Bear Attack

Abstract: Optic nerve avulsion is an exceedingly rare condition. Here, we describe a case of optic nerve avulsion in a 74-year-old man with temporal hemianopia in the contralateral eye after a bear attack. Magnetic resonance imaging (MRI) revealed separation of the optic nerve distal to the optic chiasma, whereas the high signal in diffusion-weighted imaging suggested nerve injury from the left side of the optic chiasma to the left optic tract. MRI slices parallel to the optic chiasma were obtained and used for evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Optic nerve avulsion has been reported after injuries with various causes, such as iron bars, bear attack, or falling from a tree. 7 , 8 , 9 Complete optic nerve avulsion occurred in all of these cases, but the optic nerve sheath was not intact. Mumcuoglu et al 10 reported a case of partial optic nerve avulsion with preservation of the sheath.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Optic nerve avulsion has been reported after injuries with various causes, such as iron bars, bear attack, or falling from a tree. 7 , 8 , 9 Complete optic nerve avulsion occurred in all of these cases, but the optic nerve sheath was not intact. Mumcuoglu et al 10 reported a case of partial optic nerve avulsion with preservation of the sheath.…”
Section: Discussionmentioning
confidence: 92%
“…In the literature, avulsion of the optic nerve occurred mostly at the junction of the nerve and globe, but there are cases reported with different avulsion sites. Tamase et al 7 reported a case in which the optic nerve was split distal to the optic chiasm and temporal hemianopsia developed in the contralateral eye. In our case, the avulsion site was similar to the literature and the fellow eye was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…High diffusionweighted imaging (DWI) signal of the optic chiasma to the optic tract indicated nerve injury. 25 • Disruption in the lamina cribrosa region. 23 • No pathology except sporadic vitreous hemorrhage and lamina cribrosa irregularity.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%